Mediações do rádio FM jovem na era digital - Borba, Mauro Rogério Soares (Universidade do Vale do Rio dos Sinos, 2018)
Research on the processes of FM radio mediation, especially through music, for young audiences, using the experience in broadcasters of the great Porto Alegre from the 90s. The stations Pop Rock FM and Mix FM are analyzed through interviews with their producers in the attempt to study the communicative strategies of these broadcasters, the transformations in the processes of mediatization as a function of the development of digital technologies. An empirical research based on oral history and on the orality of radio as a methodological reference. The importance of the technique in the development of radio as a means of communication, the various concepts of youth and the construction of the audience are approached on the basis of authors, being these theories put in contact with the experiences lived and activated through memory reports, trying to understand the changes and the perspective of young FM radio in times of constant technological changes, the digital era.
Keywords: Rádio; Mediação; Digital; Juventude; Música; Radio; Mediation; Digital; Youth; Music; ACCNPQ::Ciências Sociais Aplicadas::Comunicação